Effect of High Fat Diet (HFD) on Progression of Cardiomyopathy and Nephropathy - Aruna, B.; Sujith, S.; Juliet, Sanis; Ranjith, D.; Pradeep, M.; Divya, P. D.; Xavier, Adheena; Bindu Shree, R.; Vijayakrishnan, Ananthu; Deepanjaly, S. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during April, 2025 at the College of Veterinary and Animal Sciences, Pookode, to investigate the effect of a high-fat diet (HFD) on the progression of cardiomyopathy and nephropathy. Diabetes mellitus was identified as a chronic metabolic disorder characterized by persistent hyperglycemia, which contributed to severe complications such as cardiomyopathy and nephropathy. High-fat diet intake further aggravated metabolic imbalances, thereby accelerating the progression of these systemic complications. The present study evaluated cardiac and renal functions in Wistar rats fed an HFD following streptozotocin (STZ)-induced diabetes. Diabetes was induced using STZ (40 mg kg-1, i.p.) in HFD-fed rats, and animals with blood glucose levels exceeding 300 mg dl-1 four days post-induction were considered diabetic. Diabetic animals were compared with normal rats to assess metabolic, renal, and cardiac alterations. Body weight, blood glucose, total cholesterol, triglycerides, blood urea nitrogen (BUN), creatinine, and creatine kinase-myoglobin binding (CK-MB) were assessed at baseline, pre-induction, and on days 1, 14, and 28. Diabetic rats on HFD showed persistent hyperglycemia, progressive weight loss, and severe dyslipidemia. Elevated renal markers, specifically BUN and creatinine, and increased CK-MB levels indicated the progression of nephropathy and cardiomyopathy. These results demonstrated that HFD accelerated metabolic disturbances and promoted significant target organ damage in diabetes. The findings highlighted that sustained lipid abnormalities and hyperglycemia synergistically worsened myocardial and renal injury over the experimental period